1762 R.I. Pub. Laws 132 - (:unkn) unknown (My University, 1762)
And be it further Enacted by the Authority aforesaid, That no person whatsoever shall fire a gun or other fireworks within one hundred yards of the said powder house, upon the penalty of paying a fine of ten shillings lawful money, for every such offence, to be recovered by the Town Treasurer, for the use of the said Town.
Keywords: DISCHARGE